KHAZANAH PERISTILAHAN PERPADIAN PADA MASYARAKAT DAYAK BAKATIK RIOK - Thover, Thover; Syahrani, Agus; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was conducted in Sebalos backwoods, village of Sango at Sanggau Ledo District of Bengkayang Regency. This study also involved three speakers as informants to get data related to the treasury of terminology. The research question of this study was how the pattern of the perpadian lingual unit, the lexical meaning of occurrence, cultural meaning, and the level of understanding of the lexicon is.The method used in this study was descriptive in forms of qualitative research. Based on data analysis, this study got conclusions as follows (a) lingual unit form (b) terminology (c) cultural meaning and (d) level of understanding of terminology. Based on the results of data analysis, the research found that there are 104 data, age â‰¥45 years, age 25-44 years, age 12-24 years. There are 54 lexical meanings and 49 cultural meanings.Keywords: Terminology, Perpadian, Dayak Bekatik Riok